Proposta de sistema para a gestão da qualidade e da segurança de vegetais minimamente processados - Alvarenga, André Luis Bonnet (Universidade Federal de São Carlos, 2011)
The global need to ensure food quality and safety has always been a concern of primary producers, processors, distributors, consumers and governmental bodies. On the other hand, notified cases of food borne disease still cause a wide range of negative social and economic impacts worldwide. Current technology for production of Minimally Processed Vegetables (MPV) entails a series of critical steps, which can lead to product contamination by biological, chemical or physical hazards if adequate controls are not observed, and yielding potentially unsafe food products. Such concerns become even more important given that MPV`s production chains involve mostly small producers and/or enterprises in rural settings, which typically lack qualified training and specific skills. To address this challenge, the present work proposes a customized quality and safety management system for MPVs. Initially, an integrative literature search was conducted to cover topics such as quality management theory, food safety systems, MPV technology, and supply chain management as an initial step to direct a multiple case study. Field work was then performed for two MPV chains, involving a total of 18 observation units composed of rural producers, processors, shippers and distributors for retail or institutional markets, so that the system could be developed to meet the actual needs and requirements of MPV chains. Its guiding principle is the management of quality attributes of MPVs, as demanded by consumers, via the operational implications of these attributes throughout the production chain. The system also includes a performance evaluation protocol to ensure continuous process optimization. As a result, the system´s structure operates at a simple managing level, triggering systemic process vision and effective cooperation among stakeholders, while empowering them by their direct leadership and coordination of the system and ensuing processes. Finally, a working model for the proposed system is applied to minimally processed lettuce. In addition to being a tool to plan the implementation of quality and safety management protocols in this specific MPV chain, the system can also be used by MPV processors as a mainframe to guide their internal and supplier´s audits, as well as by retail and institutional companies.
Keywords: Gestão da qualidade; Segurança do alimento; Sistema de gestão; Vegetais - processamento; Cadeia produtiva; Food safety; Managing method; Minimally processed vegetables; Quality management; ENGENHARIAS::ENGENHARIA DE PRODUCAO